2017
DOI: 10.1249/mss.0000000000001230
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Responses to Aquatic Treadmill Exercise

Abstract: Findings illustrate the potential for aquatic treadmill exercise to enhance exercise-induced elevations in CBF and thus optimize shear stress-mediated adaptation of the cerebrovasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…Uniquely, the current study delineated the factors behind changes in MCAv mean during breast‐stroke swimming. Previous studies have illustrated that upright aquatic exercise (i.e., walking/running and box stepping) increases MCAv mean across a range of intensities (Pugh et al, ; Parfitt et al, ), which has been contributed, in part, to changes in PETCO 2 (Pugh et al, ). Furthermore, we illustrated that swimming shows a similar MCAv mean response as for other dynamic large muscle‐group exercise (unpublished data from our lab).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Uniquely, the current study delineated the factors behind changes in MCAv mean during breast‐stroke swimming. Previous studies have illustrated that upright aquatic exercise (i.e., walking/running and box stepping) increases MCAv mean across a range of intensities (Pugh et al, ; Parfitt et al, ), which has been contributed, in part, to changes in PETCO 2 (Pugh et al, ). Furthermore, we illustrated that swimming shows a similar MCAv mean response as for other dynamic large muscle‐group exercise (unpublished data from our lab).…”
Section: Discussionmentioning
confidence: 96%
“…As HR is lower in water than on land for the same exercise (Parfitt et al, ), a maximal swim test was undertaken 45 min after the treadmill normalV˙normalO2max test, to determine each participant’s swimming‐specific HRR. After being briefly familiarized to head‐out breast‐stroke technique and instructed to breathe as normal for swimming, participants swam head‐out breast‐stroke for incremental 2‐min stages, until exhaustion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A more recent study assessing the same question found a 21% increase in middle cerebral artery velocity (MCAv) during aquatic treadmill running compared to 12% increase during land treadmill, with matched exercise intensity levels. 8 In the study, Pugh and coworkers speculated that based upon their findings, water-based exercise training may induce greater cerebrovascular health benefits than traditional land-based exercise and that the therapeutic effect of this may be of significant health value. Although less relevant in rehabilitation practice, the question of cerebral blood flow during horizontal aquatic activity was addressed in a 2019 study of young adult recreational athletes and age-matched swimmers, finding that although there was no significant difference between prone MCAv on land or in water, prone swimming (breaststroke) increased MCAv by nearly 50%.…”
Section: Aquatic Immersion and Exercise Effects On The Central Nervoumentioning
confidence: 99%
“…As detailed in the beginning of this article, cerebral blood flow is positively affected by immersion and aquatic exercise. [7][8][9] This increase in flow velocity stimulates endothelial nitric oxide synthase (eNOS), which promotes vascular compliance, improving oxygen delivery to brain tissues. There is an association between cerebral blood flow and dementia, although the relationship is complex and also related to cerebral metabolism.…”
Section: Aquatic Therapy Use In Dementiamentioning
confidence: 99%